ENRICHMENT OF GRAIN HYDROLYSATE WITH BACTERIAL PROTEIN - Kiribayeva , A.K.; Silayev , D.V.; Baduanova , S.D.; Khassenov , B.B. (Eurasian Journal of Applied Biotechnology, 2019)
Feed enrichment with valuable nutrients for animals is a priority for the agricultural industry of Kazakhstan. This paper presents the technology of grain processing into feed preparation using lactic acid bacteria. Enzymatically hydrolyzed grain was a growing medium for the growth of lactic acid bacteria of the genus Lactobacillus. Cultivation of L.plantarum and L.salivarius bacteria in the saccharified grain hydrolysate helped to increase the total protein content in preparations by 26-45% and the enrichment of the feed preparation with glucose, lactic acid, and vitamins. This technology of grain processing into the feed preparation would be useful in terms of deep processing of grain and obtaining feed preparations containing important nutrient ingredients.